Perception of the afterlife, religiosity, and acceptance of death among the Muslin elderly. - Resano, Gelyn An G. (2018.)
This study was conducted to describe the perception of the afterlife, religiosity, and acceptance of death of the Muslim elderly. Twenty (20) Muslim elderly aged 60 and above responded to the study all of whom live in barangay Bongbong, Pantukan where the study was concentrated. An interview was conducted as well as the utilization of two instruments namely: Intrinsic Religiosity Scale (1972) and Revised-Death Attitude Scale (1994). Results showed that the elderly Muslim believe in the afterlife which is anchored by their religious beliefs. They also scored high on religiosity which indicates they showcase their faith in the religion outward. They have a Neutral Acceptance towards death indicating that death is not something they fear nor look forward to but is rather accepted as a natural course of life.
Research Project (Undergraduate, Bachelor of Arts (Psychology) College of Arts and Sciences, University of the philippines Visayas, Miagao, Iloilo.
Keywords: Muslims, Elderly -- Religiosity; Muslims, Elderly -- Acceptance of death; Muslims, El;derly -- Perseption of Afterlife